2017
DOI: 10.1176/appi.ps.201600544
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Peer-Led, Recovery-Oriented Shared Decision-Making System: A Pilot Randomized Controlled Trial

Abstract: The shared decision-making system appeared to partly improve patients' perceptions of communication and relationships with doctors but did not have a significant effect on other patient-level outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…The goal for the decision is not granted by the health professionals unilaterally, but set together with the service users through discussion (Matthias et al, 2017). It is the user's own goal, which is individual recovery-oriented (Matthias et al, 2017;Paudel et al, 2018;Woltmann, Wilkniss, Teachout, McHugo, & Drake, 2011;Yamaguchi et al, 2017). Thereafter, both parties share the service user's identified personal goal (Finnerty et al, 2019;Paudel et al, 2018;Yamaguchi et al, 2017).…”
Section: Goal Sharingmentioning
confidence: 99%
“…The goal for the decision is not granted by the health professionals unilaterally, but set together with the service users through discussion (Matthias et al, 2017). It is the user's own goal, which is individual recovery-oriented (Matthias et al, 2017;Paudel et al, 2018;Woltmann, Wilkniss, Teachout, McHugo, & Drake, 2011;Yamaguchi et al, 2017). Thereafter, both parties share the service user's identified personal goal (Finnerty et al, 2019;Paudel et al, 2018;Yamaguchi et al, 2017).…”
Section: Goal Sharingmentioning
confidence: 99%
“…Yet, there has been virtually no effort to develop strategies for integrating technical and expert-by-experience knowledge. At the same time, the evidence for peer support services in the mental health arena is increasing accumulatively in countries acknowledged to have advanced psychiatric care, including the US, Australia, and, more recently, Hong Kong [14, 19, 21, 24, 52]. For example, a recent randomized controlled trial conducted in Germany found that participants with severe mental illnesses in one-to-one peer support services showed statistically significant improvements in self-efficacy, compared with the control group [20].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps cultural issues in knowledge acquisition are unique to the development of peer support services in Hong Kong and other non-Western countries in general [44]. A recent pilot randomized controlled trial conducted in Tokyo, Japan, found that participants in a PSW-led shared decision-making intervention group reported a significantly more positive view of their relationship with their treating psychiatrists, compared to the control group [24]. Among some participants of the present study, only regular mental health workers were considered as professionals, knowledge was heavily organized in a hierarchal fashion (e.g., medical or nursing professionals hold technical knowledge and pass it to patients; see Table 1) and was not co-constructed, and advice from PSWs was to be treated with caution (see Results: Theme 2, SU24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, our analyses did control for levels of psychological distress accounting for potential differences in mental illness severity among study participants obtaining services across different mental health care settings. Finally, provider communication overlaps with other areas such as working alliance [49–51] and shared decision-making [52, 53] that have been linked to personal recovery outcomes; additional research is needed to better understand how these consumer experiences relate to one another and personal recovery. Further, some have expressed concerns that consumer experience surveys may tap into providers’ compliance with patient expectations or preferences even when they may be contraindicated (e.g., stopping medication) [54, 55], highlighting the potentially complex relationship between consumer experiences, the delivery of evidence-based care, and personal recovery.…”
Section: Discussionmentioning
confidence: 99%